Laboratory evaluation of insecticidal activity of plant essential oils against the vine mealybug, Planococcus ficus - Peschiutta, María Laura (2017)
Planococcus ficus is a principal mealybug pest of vineyards worldwide. Minthostachys verticillata and Eucalyptus globulus essential oils (EO) were evaluated as insecticidal products on P. ficus, and the main components of M. verticillata and E. globulus EO were also tested as insecticidal compounds against vine mealybug females under laboratory conditions. The results revealed that M. verticillata EO was more toxic than E. globulus EO, while pulegone (LC50 39.60 µL·L-1) was more toxic than the other constituents of the EO studied. Menthofuran, an oxidation product of pulegone by cytochrome P450 enzymes, showed an LC50 value of 63.97 µL·L-1. Thus, the mechanism of insect detoxification did not reduce the toxic potential of the pulegone. In addition, 1,8-cineole had a higher insecticidal property than its isomer 1,4-cineole. Our studies suggest that the pulegone can be a useful fumigant botanical insecticide to protect crops against vine mealybug attacks.